(untitled) (Architecture Image Studies, 2025)
Arbitration offers a flexible and expedited mechanism for settling disputes between parties. To initiate arbitration proceedings, a valid arbitration agreement between the parties is required. In some types of contracts, such as financing, parties prefer to enter asymmetrical or hybrid arbitration clauses, allowing one party to choose between arbitration and/or litigation; the other party remains confined to a single option for dispute settlement. This provides one party with a greater advantage in lieu of certain concessions to the other party, leading to unequal treatment. This study concludes that each jurisdiction has treated asymmetric clauses differently, with conflicting decisions. In most jurisdictions, courts have enforced asymmetrical arbitration clauses as valid, considering that they suit parties’ situations and the nature of the contract. For successful enforcement, asymmetric arbitration clauses must be drafted carefully, limiting the jurisdictions under which the party benefiting from the asymmetric arbitration clause may bring claims, rather than granting unlimited jurisdiction.